A Novel Inhibitor against the Bromodomain Protein 1 of the Malaria Pathogen Plasmodium Falciparum - Amann, Marius; Warstat, Robin; Rechten, Kay; Theuer, Philip; Schustereder, Magdalena; Clavey, Sophie; Breit, Bernhard; Einsle, Oliver; Hügle, Martin; Petter, Michaela; Günther, Stefan (ChemMedChem, 2025)
The rise of drug resistances in malaria necessitates the exploration of novel therapeutic strategies. Targeting epigenetic pathways could open new, promising treatment avenues. In this study, the focus is on the essential Bromodomain protein 1 (PfBDP1) of the malaria pathogen Plasmodium falciparum. Utilizing the pan-selective bromodomain inhibitor MPM6, a potent initial hit is identified and it is subsequently developed into a nanomolar binder. Through a combination of virtual docking, isothermal titration calorimetry, and X-ray crystallography, the molecular interactions of the new inhibitors with the bromodomain (BRD) of the protein (PfBDP1-BRD) are elucidated. The findings include the first co-crystallized inhibitors with the structures of PfBRD1-BRD as well as the bromodomain of the close homologous protein of Plasmodium vivax (PvBDP1-BRD). The structures provide new insights into their binding mechanisms. Further validation using conditional knockdown of PfBDP1 in P. falciparum demonstrates parasite sensitivity to the inhibitor, underscoring its potential in a targeted therapeutic approach against malaria.
CRIS-Team Scopus Importer:2025-04-18
Keywords: Antiprotozoal agents; bromodomain; drug discovery; inhibitors; Plasmodium